Aberrant Mitochondrial Fission Is Maladaptive in Desmin Mutation–Induced Cardiac Proteotoxicity. Issue 14 (17th July 2018) - Alam, Shafiul; Abdullah, Chowdhury S.; Aishwarya, Richa; Miriyala, Sumitra; Panchatcharam, Manikandan; Peretik, Jonette M.; Orr, A. Wayne; James, Jeanne; Robbins, Jeffrey; Bhuiyan, Md. Shenuarin
Abstract : Background: Desmin filament proteins interlink the contractile myofibrillar apparatus with mitochondria, nuclei and the sarcolemma. Mutations in the human desmin gene cause cardiac disease, remodeling, and heart failure but the pathophysiological mechanisms remain unknown. Methods and Results: Cardiomyocyte‐specific overexpression of mutated desmin (a 7 amino acid deletion R172‐E178, D7‐Des Tg) causes accumulations of electron‐dense aggregates and myofibrillar degeneration associated with cardiac dysfunction. Though extensive studies demonstrated that these altered ultrastructural changes cause impairment of cardiac contractility, the molecular mechanism of cardiomyocyte death remains elusive. In the present study, we report that the D7‐Des Tg mouse hearts undergo aberrant mitochondrial fission associated with increased expression of mitochondrial fission regulatory proteins. Mitochondria isolated from D7‐Des Tg hearts showed decreased mitochondrial respiration and increased apoptotic cell death. Overexpression of mutant desmin by adenoviral infection in cultured cardiomyocytes led to increased mitochondrial fission, inhibition of mitochondrial respiration, and activation of cellular toxicity. Inhibition of mitochondrial fission by mitochondrial division inhibitor mdivi‐1 significantly improved mitochondrial respiration and inhibited cellular toxicity associated with D7‐Des overexpression in cardiomyocytes. Conclusions: Aberrant mitochondrial fission results in mitochondrial respiratory defects and apoptotic cell death in D7‐Des Tg hearts. Inhibition of aberrant mitochondrial fission using mitochondrial division inhibitor significantly preserved mitochondrial function and decreased apoptotic cell death. Taken together, our study shows that maladaptive aberrant mitochondrial fission causes desminopathy‐associated cellular dysfunction.